Bilingual E-Magazine: The Development of Digital Teaching Resource on Students’ Literacy of Environmental Pollution - Vonti, Lungguh Halira; Indriyani; Ganeswara, M. Ginanjar; Rahmah, Mursidah; Rosyid, Abdul (Universitas Pendidikan Ganesha, 2024)
Based on research in ASIA, Indonesia is still in the lowest position in the term of literacy. Moreover, the students’ interest of using and exploring conventional teaching materials is also still low. One of the materials given in every level of education now is PLH or Environment Education. The government concerns about environment education should be supported by the availability of appropriate and interactive teaching media. Therefore, this study aims to develop and produce digital teaching media for the subject under the topic of environment pollution as well as improving students’ literacy and understanding of the subject material in PLH subject. The research employed research and development design started with analysis process, designing process, development process, implementation and evaluation process. The result of the research is E-Magazine as one of the Learning resources that contain learning materials that are displayed attractively with more interesting features such as images, videos, and interesting display. The result of the product’s implementation shows that the students’ digital literacy of environmental pollution is increased by the score of 82,11%. Based on results analysis of the students’ understanding of the environmental pollution for the subject, the N-gain score was 0,83 and it was higher than 0,70 as the standard for high level effectiveness.